Persepsi Siswa tentang Perilaku Kekerasan Seksual dan Implikasinya terhadap Layanan BK - Certha Adarya Anugrahesa; Yeni Karneli (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2024)
Sexual violence is a serious problem that needs to be addressed in Indonesia, including within school environments, characterized by an increase in the number of sexual violence incidents and the prevalence of cases being uncovered. This phenomenon is highly concerning among students, as evidenced by several data points indicating a significant occurrence of sexual violence among students. The aim of this study is to describe students' perceptions of sexual violence, examined through the cognitive, affective, and conative aspects. The study population consists of 7th and 8th grade students of SMPN 41 Padang for the academic year 2023/2024, totaling 313 students. The sampling technique used is stratified random sampling with a sample size of 175 students. The instrument utilized in this study is a questionnaire. Data obtained were analyzed using percentages. The results of this research indicate that: (1) students' perception of sexual violence behavior in terms of cognitive aspects falls into the positive category, meaning that students have a good understanding of behaviors that constitute sexual violence, (2) students' perception of sexual violence behavior in terms of affective aspects falls into the positive category, meaning that students can feel behaviors that are considered sexual violence and are aware that such behaviors should be avoided, (3) students' perception of sexual violence behavior in terms of conative aspects falls into the positive category, indicating that students are capable of taking positive actions to avoid or prevent sexual violence behavior from occurring. Overall, students have a positive perception of sexual violence, showing a good understanding of sexual violence behavior and the ability to interpret it well, thereby avoiding behaviors associated with sexual violence, which will contribute to a more effective learning process for students in school.